SKRINING SENYAWA INHIBITOR H2 DARI KAYU MANIS (Cinnamomum verum J.Presl) - Samsul Hadi; Diah Aulia Rosanti; Desiya Ramayanti Azhara; Kunti Nastiti (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
Digestive tract disorders, especially gastric disorders, are often experienced by people. One drug to treat this disorder has a mechanism of blocking the H2 receptor. This research was conducted to find compounds from C.verum which have the stability of bind to H2 receptors. The method used is protein modeling with swiss-model, docking with PLANTS (CHEMPLP) and activity prediction. The test results obtained that the docking score was ?- amorphene (-65,79), ?-bergamotene (-65,48), ?-copaene (-66,62), ?-cubebene (-66,46), Cadinene (-64 , 79), Camphor (-52.15), Caryophyllene (-62.61), Cinnamaldehyde (-68.17), Epicatechin (-80.43), Ergosterol (-85.24), Eugenol (-67.35), Hydrocinnamaldehyde (-65,53), Quercetin (-74,38), Protocatechuic acid (-71,49), Stigmasterol (-88,88), 4- (2,3-dihydro-3- (hydroxymethyl) - 5- (3-hydroxypropyl) -7- (methoxy) benzofuranyl] -2-methoxyphenyl (-85,29). Combined with the probability activity of compounds that have the potential to be further developed are Epicatechin and urolignoside.